(untitled) (Fisioterapia e Pesquisa, 2020)
To verify the relationship between the general movements assessment (GMA) and obstetric variables (maternal breastfeeding, pregnancy complications, gestational medication, alcohol consumption during gestation, smoking during gestation, intercurrence at birth, need for neonatal ICU admission, and need for mechanical ventilation), the presence of psychological risk and the outcome in language, cognitive, and motor development at 18 and 24 months. In total, 42 infants composed the sample and were filmed until the age of four months, in spontaneous movement for 15 minutes. The general movements were evaluated by videos using the qualitative evaluation of Prechtl and they were classified as normal or abnormal depending on the presence of fluency, complexity, and variability. The data were statistically analyzed regarding obstetric variables and the presence of psychological risk evaluated by the PREAUT signs, clinical indicators of developmental risk and M-CHAT. It was verified that there was no association between the GMA method and the analyzed variables. It is believed that because the sample was mostly composed of full-term infants or late premature infants without intercurrence, and the evaluation was transverse in a single moment, it was not possible to analyze whether the movements evaluated as abnormalities were or were not transient. The change of movements by the Prechtl method was not associated with the variables analyzed in the sample of late and term premature infants.